Factors That Influence Purchasing Decisions with Brand Image as An Intervening Variable - Rizka Arsyntha Permatasari; Chevy Fantastic; Eka Febryanti; Eka Maria Susanti; Eva Agustina; Rezita Meylani Yopi; Rostiar Situmorang; Muammar Khaddafi (Lafadz Jaya Publisher, 2024)
This study aims to determine the effect of product quality on purchasing decisions, the effect of promotion on purchasing decisions, the effect of trust on purchasing decisions, the effect of convenience on purchasing decisions, the effect of price on purchasing decisions, the effect of product quality, promotion, trust, convenience and price on purchasing decisions, the effect of product quality on purchasing decisions through brand image, the influence of Promotion on Purchasing Decisions through Brand Image, the influence of Trust on Purchasing Decisions through Brand Image, the influence of Convenience on Purchasing Decisions through Brand Image, the influence of Price on Purchasing Decisions through Brand Image, the influence of Purchasing Decisions on Brand Image and the influence between Product Quality, Promotion, Trust, Convenience and Price on Purchasing Decisions through Brand Image in the Shopee marketplace. This research uses quantitative research. The population in this study were Batam City students who used the Shopee marketplace. Researchers used the hair method, so that a sample of 300 respondents was obtained with a formula of 1 question for 10 respondents. The sampling approach in this study was nonprobability sampling using incidental sampling. Independent variables include product quality (X1), promotion (X2), trust (X3), convenience (X4), price (X5). then the dependent variable of this study is the purchase decision (Y), and the intervening variable is Brand Image (Z). The data collection method used a questionnaire, then the data was analyzed using the Statistical Program for Social Science. The results show H1, H2, H3, H8, H11 are rejected because the Sig. value is greater than 0.05. Then the results show H4, H5, H6, H7, H9, H10, H12, H13 are accepted because the Sig. value is smaller than 0.05.